1996
DOI: 10.1063/1.363534
|View full text |Cite
|
Sign up to set email alerts
|

High-energy and high-fluence proton irradiation effects in silicon solar cells

Abstract: We have examined proton irradiation damage in high-energy (1–10 MeV) and high-fluence (≳1013 cm−2) Si n+-p-p+ structure space solar cells. Radiation testing has revealed an anomalous increase in short-circuit current Isc followed by an abrupt decrease and cell failure, induced by high-fluence proton irradiation. We propose a model to explain these phenomena by expressing the change in carrier concentration p of the base region as a function of the proton fluence in addition to the well-known model where the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 3 publications
2
41
0
Order By: Relevance
“…The highly energetic particles interacting with solar cells induce defects in the semiconductor lattice and, consequently, deteriorate the solar cell performance [3]. The performance degradation of solar cells subjected to energetic electrons and protons in laboratories is well characterized [4][5][6][7][8][9]. It was observed that the space solar figures of merit (the short circuit current , the open circuit voltage , the maximum output power , the fill factor and the conversion efficiency ) decrease linearly with the logarithm of the fluence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly energetic particles interacting with solar cells induce defects in the semiconductor lattice and, consequently, deteriorate the solar cell performance [3]. The performance degradation of solar cells subjected to energetic electrons and protons in laboratories is well characterized [4][5][6][7][8][9]. It was observed that the space solar figures of merit (the short circuit current , the open circuit voltage , the maximum output power , the fill factor and the conversion efficiency ) decrease linearly with the logarithm of the fluence.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some silicon solar cells, the short circuit current does not strictly follow this behavior. Instead, it initially decreases, then at a certain fluence it slightly increases before decreasing again sharply [2,5,7,9,[13][14][18][19]. This slight recovery of the short circuit current is usually attributed to a type conversion of the base (from n to p-type for example) [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that recombination centres introduced by electron irradiation decreases the minority carrier diffusion length and at low doses of electron irradiation, the degradation is due to the decrease in minority carrier diffusion length [21]. It is also reported that most of the defects introduced upon irradiation can be removed by annealing [22].…”
Section: Variation Of Dark I-v Characteristics With Temperature Forwamentioning
confidence: 99%
“…[24][25][26] Electrically active defects form trap levels in the energy bandgap where charge carriers undergo COMMUNICATIONS 52 www.advmat.de recombination through deep-level energy states, which reduces the hole density and increases the resistivity. The resistivity close to the surface of p-type silicon as a function of 2 MeV helium ion irradiation dose is plotted in Figure 3a, based on the measured values of defect production and trapping rates, [27] with changes in hole mobility with doping concentration taken into account. Of note is the rapid increase in resistivity above a certain dose threshold.…”
mentioning
confidence: 99%